Stakeholder analysis in the implementation of forestry policies: the case of the Asirmi - Rodríguez-Aguilar, Oliver; Trench, Tim (Instituto de Ecología, A.C., 2020)
Decentralization within the forestry sector has relied on Regional Forestry Associations (ARS) and independent Forestry Technicians (PSTF) to implement government policies in Forest Management Units (Umafor). The goal of this study was to describe and analyze the roles played by the National Forestry Commission (Conafor), the Miramar Region Forestry Association (Asirmi) and the associated Forestry Technician in the implementation of the Special Programme for the Conservation, Restauration and Sustainable Use of the Lacandon Rainforest (PESL) in Chiapas between 2010 and 2015. The sample method used was the snowball technique and 49 semi-structured interviews were carried out. This was complemented with participant observation and field trips. Conafor’s participation was increasingly limited to approving (or not) applications for the financing of forestry projects due to budget cuts. The participation of the forestry association was enlisted as a requirement for the approval of projects. The Forestry Technician participated in the promotion, management and operation of the projects. Therefore, his actions were key to the approval of projects for the association and the ways in which these different projects were developed on the ground.